(untitled) (Revista Contexto & Educação, 2023)
The article aims to analyze the places occupied by gender issues and the idea of integral human formation in the guiding documents of the Centro Estadual de Educação Profissional (CENEP) Senador Jessé Pinto Freire (SJPF), located in Natal/RN. To analyze the Political-Pedagogical Project (PPP) and the Institutional Political-Pedagogical Project (PPPI), a qualitative and exploratory methodology was used with the help of Textual Discourse Analysis (TDA). The theoretical framework focused on the literature about gender studies, in dialogue with theoreticians of Professional Education. The results indicate that the documents are aligned with the perspective of an Integral Human Formation. However, it was also diagnosed a strong silencing of gender issues, invisibilizing the subalternization of women in Professional Education.